Meningkatkan Hasil Belajar Akuntansi dengan Menggunakan Strategi PAILKEM Model Diskusi Kelompok pada Peserta Didik Kelas X Akuntansi di SMKN-1 Katingan Hilir - Nopitae Sari; Sonedi Sonedi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to determine the activities of students and know the learning outcomes. The method used by researchers is to use the Classroom Action Research (CAR) design. For data collection techniques used are observations and tests with the research subject is class X Accounting for SMK Negeri 1 Katingan Hilir 2015/2016 Academic Year. The data analysis technique used is qualitative data analysis and quantitative data analysis. The results showed that: (1) learning activities of students of class X Accounting II at SMK Negeri 1 Katingan Hilir using the more active PAILKEM strategy, (2) there was an increase in accounting learning costs for students of class X Accounting II at SMK Negeri 1 Katingan Hilir using the PAILKEM strategy which shows Accounting learning outcomes in the first cycle obtained an average of 76.20 with classical completeness of 65.51% and in the second cycle the median was 82.41 with artistic integrity of 89.65%.